2004
DOI: 10.5713/ajas.2004.467
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Fungal Treated Wheat Straw in the Diet of Late Lactating Cow

Abstract: Eight primiparous Holstein cows, in late lactation (255±10 days in milk) and yielding 10.3±1.3 kg/d of 4% fat corrected milk (FCM) were allocated into two groups randomly. Two diets containing 30% wheat straw either untreated (UWS) or treated with Pleurotus ostreatus (FTWS) were offered as total mixed ration (TMR). In vivo digestibility of the diets was determined, using acid insoluble ash as a marker. Daily milk production was recorded and milk samples were collected and analysed. Diet FTWS resulted in signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
1
17
2
Order By: Relevance
“…The insignificant reduction recorded for groups G2 and G3 could be attributed to the recorded insignificant differences in intake of DM, CP and TDN as well as in nutrient digestibility parallel to the insignificant decrease in average daily gain. The present findings are disagree with the findings Items T1 T2 T3 T1 T2 T3 T1 T2 T3 of Fazaeli et al (2004), Kabirifard et al (2007), Khattab et al (2009), Omer et al (2012 and Shrivastava et al (2012), who reported a positive response in terms of nutrient utilization, nitrogen balance as well as body weight gain associated with utilization of biological treated crop residues in animal rations.…”
Section: Rumen Liquor Parameterscontrasting
confidence: 56%
See 1 more Smart Citation
“…The insignificant reduction recorded for groups G2 and G3 could be attributed to the recorded insignificant differences in intake of DM, CP and TDN as well as in nutrient digestibility parallel to the insignificant decrease in average daily gain. The present findings are disagree with the findings Items T1 T2 T3 T1 T2 T3 T1 T2 T3 of Fazaeli et al (2004), Kabirifard et al (2007), Khattab et al (2009), Omer et al (2012 and Shrivastava et al (2012), who reported a positive response in terms of nutrient utilization, nitrogen balance as well as body weight gain associated with utilization of biological treated crop residues in animal rations.…”
Section: Rumen Liquor Parameterscontrasting
confidence: 56%
“…During the last years, many efforts have been employed to increase their feeding values by biological treatments (Liu and Orskov, 2000;Zhu et al, 2005;Eun et al, 2006), which many studies indicated that the biological treatments tend to increase in vitro digestibility of tested materials (Zadrazil and Puniya, 1995;Sharma and Arora, 2010) and in vivo digestibility (Chen et al, 1995;Akinfemi et al, 2009;Arora and Sharma, 2009). Moreover, Fazaeli et al (2004), Kabirifard et al (2007), Omer et al (2012), Shrivastava et al (2012) and El-Bordeny et al (2015) reported a positive response in terms of nutrient utilization, nitrogen balance as well as body weight gain associated with using of biologically treated crop residues in animal feeding. However, little researches have been done to evaluate effect of inclusion biologically treated crop residues on animal physiological performance.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in cell wall components might be due to the breakdown of lignocelluloses bonds resulting into hydrolysis of cellulose by fungi and bacteria (El-Ashryet al, 2002;El-Shafie et al, 2007;Fayed et al, 2009 andMahrous et al, 2010). Fazaeli et al (2004) noted that fungi treatment solubilize and utilize the cell wall components as carbon source and thus change the ratio of insoluble to soluble carbohydrates in the by-products. The result of treatment inoculated with EM agree with the finding of Yonatan (2010) who reported that treatment of coffee husk with EM decreased the cell wall components as compared to the untreated husk.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have involved feeding white rot fungi to animals. A notable exception is the study of Fazaeli et al (2004) in which treatment of wheat straw with a lignin-selective strain, Pleurotus ostreatus (P-41), increased DMI (12.2 vs. 10.6 kg/d), DMD (58.8 vs 52.3%), NDFD (42.3 vs. 34.3%), milk yield (9 vs. 7.5 kg/d), and BW gain (743 vs. 272 g/d) of dairy cattle in late lactation, when the treated and untreated straw were fed as 30% of a TMR. Similarly, Shrivastava et al (2014) reported greater DMI (per kg of metabolic BW), DMD (57.82 vs. 52.07%), NDFD (53.3 vs. 45.8%), and 50 g/d higher average BW gain, when buffalo calves were fed wheat straw treated with Crinipellis sp.…”
Section: White-and Brown-rot Fungimentioning
confidence: 99%